Preparation of pellets from uranium dioxide without binder - Odeychuk, M.P.; Sirenko, S.A. (Functional Materials, 2014)
In the article the considered method of making of fuel pellets is from UO₂ without connective. This method allows to make fuel pellets with enhanceable technico-operating by descriptions.